2014
DOI: 10.1530/erc-13-0283
|View full text |Cite
|
Sign up to set email alerts
|

Androgen receptor roles in hepatocellular carcinoma, fatty liver, cirrhosis and hepatitis

Abstract: Summary Androgen/androgen receptor (AR) signaling plays important roles in normal liver function and in progression of liver diseases. In studies of non-cancerous liver diseases, AR knockout mouse models of liver disease have revealed that androgen/AR signaling suppresses the development of steatosis, virus-related hepatitis, and cirrhosis. In addition, studies have shown that targeting AR in bone marrow-derived mesenchymal stem cells (BM-MSCs) improves their self-renewal and migration potentials, thereby incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
117
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 145 publications
(124 citation statements)
references
References 135 publications
(186 reference statements)
6
117
0
1
Order By: Relevance
“…The further investigation should focus on the detection of targeting properties of these ligands for preclinical trials and explore new target sites on membrane of hepatoma cells. Apart from ligands mentioned earlier, there are ligands whose receptors were found to have increased expression on HCC cells or play a role in HCC development, such as adenosine A2b receptor, 264 gamma-aminobutyric acid A receptor theta subunit, 265 androgen receptor, 266 E prostanoid receptor, 267 mitogenic insulin receptor A, 268 receptor of insulin-like growth factor 2, 269 and so on. On the other hand, the spatial properties of ligands can affect the targeting performance.…”
Section: Resultsmentioning
confidence: 99%
“…The further investigation should focus on the detection of targeting properties of these ligands for preclinical trials and explore new target sites on membrane of hepatoma cells. Apart from ligands mentioned earlier, there are ligands whose receptors were found to have increased expression on HCC cells or play a role in HCC development, such as adenosine A2b receptor, 264 gamma-aminobutyric acid A receptor theta subunit, 265 androgen receptor, 266 E prostanoid receptor, 267 mitogenic insulin receptor A, 268 receptor of insulin-like growth factor 2, 269 and so on. On the other hand, the spatial properties of ligands can affect the targeting performance.…”
Section: Resultsmentioning
confidence: 99%
“…Androgen/AR signals play important roles in normal liver function and in the development of liver diseases including HCC (Ma et al, 2014). Previous studies revealed a male predominance in HCC, which suggested that androgen/AR signals may promote hepatocarcinogenesis (Yeh and Chen, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Concordant with the male predominance of HCC, the sex hormone receptor androgen receptor (AR) plays a dominant role in hepatocarcinogenesis [17]. Our prior work underpinned cell cycle-related kinase (CCRK, also known as cyclin-dependent kinase 20) as an oncogenic effector of AR in HCC [18,19].…”
Section: Introductionmentioning
confidence: 99%